The Informal Economy: A Threat to the Dream of Emergent African Economies? - (:unkn) unknown (My University, 2019)
Since the early 2000s, the African continent has been experiencing a cycle of strong economic growth, but the structural transformations needed for its economies to truly emerge have been slower in coming. Quality jobs remain scarce, and informal employment remains the norm in the labour market. The heterogeneity of this informal economy makes it complex to define and harder to be factored into public policy. The objectives of supporting and modernizing production units and of formalizing and bringing them into line with a certain number of standards and regulations are two complementary sides of any economic policy aimed at tackling the challenges that such informality poses for emerging economies.
Keywords: African Research